Aluminum-incorporated p-CuO/n-ZnO photocathode coated with nanocrystal-engineered TiO2 protective layer for photoelectrochemical water splitting and hydrogen generation. Issue 25 (7th June 2018) - Masudy-Panah, Saeid; Eugene, Y.-J. Kong; Khiavi, Negar Dasineh; Katal, Reza; Gong, Xiao
Abstract : The poor photocorrosion stability and low photovoltage of cupric oxide (CuO) are the main limiting factors of CuO-based photocathodes for solar-driven photoelectrochemical (PEC) water splitting and hydrogen evolution. Abstract : The poor photocorrosion stability and low photovoltage of cupric oxide (CuO) are the main limiting factors of CuO-based photocathodes for solar-driven photoelectrochemical (PEC) water splitting and hydrogen evolution. In this paper, we demonstrate a highly efficient CuO-based photocathode fabricated on a glass substrate coated with fluorine-doped tin oxide (FTO). Incorporating aluminum (Al) into the thin CuO film (CuO:Al) and inserting a thin CuO interfacial layer between the CuO:Al film and the FTO-coated glass substrate is shown to improve the photocorrosion stability of the CuO and increase the photocurrent without increasing the dark current. We also demonstrate that depositing a layer of ZnO to form a buried p-(CuO/CuO:Al)/n-ZnO:Al heterojunction and controlling the carrier concentration and conductivity of the ZnO through the incorporation of Al can significantly improve the photovoltage and PEC activity of the photocathode, leading to a record-high photovoltage of ∼0.53 VRHE . By capping the photocathode with a crystal-engineered TiO2 protective layer, we are able to significantly stabilize the photocathode against photocorrosion and further improve the PEC activity of the final p-(CuO/CuO:Al)/n-ZnO:Al/TiO2 /Au–Pd photocathode, resulting in record-high photocurrent density of ∼5.4 mA cm −2 and photocorrosion stability of ∼87% after 5 hours.